PELAKSANAAN PEMBELAJARAN MENULIS CERITA FANTASI: STUDI KASUS DI KELAS VII SMP NEGERI 4 SURAKARTA - Dimas Putra Dwipa; Nugraheni Eko Wardani; Atikah Anindyarini (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
The aims of this research are: 1) Describe and explain learning planning to write fantasy story to students of class VII H SMP N 4 Surakarta. 2) Describe and explain the implementation of learning to write fantasy stories of class VII H students of SMP N 4 Surakarta. 3) Describe and explain the obstacles to learning to write fantasy stories of class VII H students of SMP N 4 Surakarta. 4) Describe and explain the efforts to overcome the obstacles to learning to write fantasy stories of class VII H students of SMP N 4 Surakarta. This research is a case study with qualitative research methods. In this study, data sources were obtained from informants who were Indonesian language teacher and students in VII H of SMP N 4 Surakarta. While the data obtained is in the form of documents that are relevant to the focus of the research, namely the results of interviews, syllabus, and lesson plans that are owned by the teacher. The subjects in this study were VII H Indonesian Language subject teacher and VII H’s students at SMPN 4 Surakarta. The research technique used in selecting this subject is by using a purposive sampling technique. The technique used in collecting data in this study is observation, interviews, and document analysis. In this study triangulation techniques were carried out. The selected triangulation can be in the form of data triangulation and methods. In this study, data was analyzed by means of data reduction, data display, conclusions drawing.